Coming Home to a Foreign Country Xiamen and Returned Overseas Chinese, 1843-1938 - Ong, Soon Keong 1969- (Cornell University Press, 2021)
Ong Soon Keong explores the unique position of the treaty port Xiamen (Amoy) within the China-Southeast Asia migrant circuit and examines its role in the creation of Chinese diasporas. Coming Home to a Foreign Country addresses how migration affected those who moved out of China and later returned to participate in the city's economic revitalization, educational advancement, and urban reconstruction. Ong shows how the mobility of overseas Chinese allowed them to shape their personal and community identities for pragmatic and political gains. This resulted in migrants who returned with new money, knowledge, and visions acquired abroad, which changed the landscape of their homeland and the lives of those who stayed. Placing late Qing and Republican China in a transnational context, Coming Home to a Foreign Country explores the multi-layered social and cultural interactions between China and Southeast Asia. Ong investigates the role of Xiamen in the creation of a China-Southeast Asia migrant circuit; the activities of aspiring and returned migrants in Xiamen; the accumulation and manipulation of multiple identities by Southeast Asian Chinese as political conditions changed; and the motivations behind the return of Southeast Asian Chinese and their continual involvement in mainland Chinese affairs. For Chinese migrants, Ong argues, the idea of "home" was something consciously constructed. Ong complicates familiar narratives of Chinese history to show how the emigration and return of overseas Chinese helped transform Xiamen from a marginal trading outpost at the edge of the Chinese empire to a modern, prosperous city and one of the most important migration hubs by the 1930s